A case study on the effect of yoga on the posture of females with scoliosis - Calvelo, Emirose Gellind C. 1998- (College of Human Kinetics, University of the Philippines Diliman, 2019)
Scoliosis is a condition of the spine where it rotates to a certain degree which results to imbalances in the body. Because of these imbalances, the posture of the person may be affected depending on the severity of the condition. Orthopedics may suggest ways on correcting the posture of a person with scoliosis like spinal surgery, wearing orthopedic braces, physical therapy, and by engaging in sports physical activity, and exercise. While some may claim these methods as effective, these methods have their own advantages and disadvantages. Methods like spinal surgery and orthopedic bracing, though claimed effective, are expensive and may not be feasible for patients who are not financially stable. Sports and other physical activities however can be done at a cheaper price. Yoga is one of the exercises that orthopedics suggests to patients. With this in mind, this study aims to know the effects of yoga on the posture of females with scoliosis. The participants will be 5 females, 3 of which will have mild scoliosis and the other 2 with moderate scoliosis. Their posture will be assessed using posture assessment grids and charts and they will be answering questionnaires regarding the back pain they are feeling due to their scoliosis. The participants will be asked to attend yoga classes twice or thrice a week for a month. If by the end of the study their posture and back pain improves, this can be recommended as a cheaper alternative to improve posture and alleviate back pain.